The Role of Radiant Storytelling in Developing Children's Memory and Information Retention - Ainu Zuhriyah (CV. AGRAPANA MEDIA, 2025)
This study examines the role of serial storytelling in enhancing memory and information retention in early childhood. Serial storytelling is a learning method that presents stories continuously, encouraging children to remember, understand, and connect information with prior experiences. This research uses a qualitative approach through library research, reviewing literature on learning strategies, child cognitive psychology, and the implementation of storytelling in early childhood education. The findings indicate that serial storytelling plays several important roles, namely: improving short-term and long-term memory, fostering interest and motivation to learn, enhancing language skills and story comprehension, and stimulating creativity and imagination. When applied appropriately, this method strengthens children's cognitive, social, and emotional skills holistically. Serial storytelling becomes an effective strategy that combines entertainment and learning, allowing children to learn in a fun and continuous manner. This study provides important implications for educators in designing learning activities that stimulate memory, information retention, and optimal child development.